Class, Labor, and the Home-Front Detective: Hammett, Chandler, Woolrich, and the Dissident Lawman (and Woman) in 1940s Hollywood and Beyond - Broe, Dennis (Social justice, 2005)
Part of a special issue on the many faces of violence. The writer traces the movement of the home-front detective through selected key texts and argues that this movement is congruent with that of labor as a whole. He demonstrates how the transition by the home-front detective toward operating outside of the law accelerated as World War II continued, with business profits increasing and wages stagnating. He contends that, in a similar way, the contemporary return to the conformist home-front detectives in such television series as Dragnet and C.S.I. might soon cede to more dissident detectives as the promised gains of the post-September 11 “endless” war yield less benefit to audiences.